A IMPLEMENTASI METODE LEAST SQUARE DALAM MEMPREDIKSI PATTY CASH DI JANK-JANK WINGS BLITAR - siti ro diyah (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2020)
AbstractPatty cash is one of the major financial transactions, which encourages companies to control and connect every major financial transaction. Patty cash itself is usually used to finance company operations. As a company classified as quite large, the wings of Blitar always issue quite large financial transactions. Frequent lending of turnover money for shopping causes confusion in money management and is not conducive. The Least Square method is the Least Square method is a method used to predict the future based on past data, forecasting will be more accurate so that more data is used. From what is done, the test results show that the respondents strongly agree that the application system will be used, while the MAPE results with a value of 16% means that the ability to forecast using the Least Square method is good.Keywords: Least Square, Patty Cash, Prediction, Jank-Wings Blitar